2014
DOI: 10.5812/ircmj.16433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coenzyme Q10 Supplementation on Serum Lipoproteins, Plasma Fibrinogen, and Blood Pressure in Patients With Hyperlipidemia and Myocardial Infarction

Abstract: Background:Low plasma concentrations of coenzyme Q10 (CoQ10) have been associated with concentration of lipoproteins and other factors contributing to coronary heart diseases.Objectives:The present investigation aimed to improve the blood pressure and serum lipoproteins concentration in patients with myocardial infarction (MI) by CoQ10 supplementation.Patients and Methods:In this randomized double-blinded controlled clinical trial, 52 Iranian patients with hyperlipidemia and MI were recruited to examine the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 30 publications
2
16
0
1
Order By: Relevance
“…In partial agreement with our results, several studies with animals have suggested that CoQ 10 significantly decreased blood triglyceride in a high fat diet fed rats or hepatic lipid concentration with no effect on plasma lipid components in atherogenic rabbits [27,28]. However, a study with humans [29] demonstrated that a CoQ 10 supplement to patients with hyperlipidemia improved serum HDL-cholesterol as well as the ratios of TC/HDL-C and LDL/HDL-C, suggesting that dietary CoQ 10 might be associated with a reduction in the risks of myocardial infarction in patients.…”
Section: Discussionsupporting
confidence: 93%
“…In partial agreement with our results, several studies with animals have suggested that CoQ 10 significantly decreased blood triglyceride in a high fat diet fed rats or hepatic lipid concentration with no effect on plasma lipid components in atherogenic rabbits [27,28]. However, a study with humans [29] demonstrated that a CoQ 10 supplement to patients with hyperlipidemia improved serum HDL-cholesterol as well as the ratios of TC/HDL-C and LDL/HDL-C, suggesting that dietary CoQ 10 might be associated with a reduction in the risks of myocardial infarction in patients.…”
Section: Discussionsupporting
confidence: 93%
“…The results reported on the effects of CoQ10 supplementation on the lipid ratios are controversial. Similar to our study, Mohseni et al 13 observed that supplementation with 200 mg per day of CoQ10 for 12 weeks in patients with hyperlipidemia, significantly decreases TC/HDL-C, and LDL-C/ HDL-C ratios. In the study of Ahmadvand et al 29 receiving CoQ10 in alloxan-induced type 1 diabetic rats, could significantly prevent the increase of atherogenic index, atherogenic coefficient, TC/ HDL-C ratio and LDL/HDL-C ratio compared with the untreated diabetic animals.…”
Section: Discussionsupporting
confidence: 91%
“…A well-known and important risk factor for incidence of CVD in patients with T2DM is dyslipidemia. Risk development of CVD in T2DM patients can be predicted through lipid ratios and AIP values [12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations